City competition for the creative class. - Buettner, Thiess; Janeba, Eckhard (My University, 2013)
This paper explores the conditions under which decentralization and fiscal competition lead to a policy of subsidizing cultural activities. A theoretical analysis discusses these subsidies as a form of local public good provision which makes a city more attractive to highly educated individuals. The analysis shows that the incentive to provide the public good is particularly strong, if institutional restrictions prevent local governments from adjusting their tax structure. An empirical analysis considering the case of public theaters in Germany supports the view that public subsidies attract highly educated individuals and capitalize in the earnings of workers with basic education. Given institutional restrictions, the empirical effects suggest that local jurisdictions face a substantial fiscal incentive to subsidize cultural activities.
Keywords: Kommunalpolitik; Kultur; Subvention; Investition; Wirtschaftsförderung; Standortpolitik; Kreatives Milieu; Kreativwirtschaft; Städtewettbewerb; Wirtschaftsstandort; Weicher Standortfaktor